SLANG EXPRESSIONS ANALYSIS IN GROWN UPS 2 MOVIE - Jimmi Jimmi (Wanastra: Jurnal Bahasa dan Sastra, 2014)
Language is a tool of communication it means as a tool of communication there are many variations in the development styles of language one of them is slang that is becoming a new style of language among young people, especially teenagers. Talking about slang expressions can not be separated from linguistics because it is the scientific study of human language and slang is part of linguistics. current slang expressions is easy to find in various media, one of them is movie. The usage of slang in the movie is found in the dialogue script, one movie that use slang expressions is Grown Ups 2 movie. The method that is used by the writer is descriptive qualitative method which is collecting the data from watching movie, analyze the data and give conclusions. After analyzing the slang expressions in the movie script, the writer find two findings. First, there are two types of slang, primary slang dude, gangsta and fella and then is secondary slang deadbeat, chicken and fugly. Second, type of slang mostly used in this movie is primary slang.